Roles of Autotaxin/Autotaxin-Lysophosphatidic Acid Axis in the Initiation and Progression of Liver Cancer - She, Sha; Zhang, Qian; Shi, Jinzhi; Yang, Fan; Dai, Kai (Frontiers in Oncology, 2022)
Autotaxin (ATX) is a secreted glycoprotein and catalyzes the hydrolysis of lysophosphatidylcholine to lysophosphatidic acid (LPA), a growth factor-like signaling phospholipid. ATX has been abundantly detected in the culture medium of various cancer cells, tumor tissues, and serum or plasma of cancer patients. Biological actions of ATX are mediated by LPA. The ATX-LPA axis mediates a plethora of activities, such as cell proliferation, survival, migration, angiogenesis, and inflammation, and participates in the regulation of various physiological and pathological processes. In this review, we have summarized the physiological function of ATX and the ATX-LPA axis in liver cancer, analyzed the role of the ATX-LPA axis in tumorigenesis and metastasis, and discussed the therapeutic strategies targeting the ATX-LPA axis, paving the way for new therapeutic developments.